Host-mediated regulation of superinfection in malaria. - Portugal, S; Carret, C; Recker, M; Armitage, A; Gonçalves, L; Epiphanio, S; Sullivan, D; Roy, C; Newbold, C; Drakesmith, H; Mota, M (2011)
In regions of high rates of malaria transmission, mosquitoes repeatedly transmit liver-tropic Plasmodium sporozoites to individuals who already have blood-stage parasitemia. This manifests itself in semi-immune children (who have been exposed since birth to Plasmodium infection and as such show low levels of peripheral parasitemia but can still be infected) older than 5 years of age by concurrent carriage of different parasite genotypes at low asymptomatic parasitemias. Superinfection presents an increased risk of hyperparasitemia and death in less immune individuals but counterintuitively is not frequently observed in the young. Here we show in a mouse model that ongoing blood-stage infections, above a minimum threshold, impair the growth of subsequently inoculated sporozoites such that they become growth arrested in liver hepatocytes and fail to develop into blood-stage parasites. Inhibition of the liver-stage infection is mediated by the host iron regulatory hormone hepcidin, whose synthesis we found to be stimulated by blood-stage parasites in a density-dependent manner. We mathematically modeled this phenomenon and show how density-dependent protection against liver-stage malaria can shape the epidemiological patterns of age-related risk and the complexity of malaria infections seen in young children. The interaction between these two Plasmodium stages and host iron metabolism has relevance for the global efforts to reduce malaria transmission and for evaluation of iron supplementation programs in malaria-endemic regions.